Effect of Nursery Phase Feeding Budget and Weaning Body Weight on Nursery Pig Growth Performance, Fecal Dry Matter, and Economics - Julian Arroyave; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 270 pigs (initially 13.5 ± 0.59 lb) were used to evaluate the effects of phase feeding budget and weaning weight on nursery performance, fecal dry matter, and economics. At weaning, pigs were sorted by body weight (BW) and then randomly assigned to one of the three dietary treatments in a 3 × 3 factorial design with main effects of nursery phase feeding budget (high, medium, or low) and BW (light, medium, or heavy). There were five pigs per pen and six pens per treatment. The feed budgets for phases 1 and 2 were 4, 2, 0, and 12, 8, 4 lb/pig for high, medium, and low nursery feeding duration, respectively. All pigs were then fed a common phase 3 thereafter. Each BW category (light, medium, and heavy) contained 33% of the pigs. Phase 1 was formulated using spray-dried bovine plasma, processed soy product, and spray-dried whey, and was formulated to 17.5% lactose with 16.3% soybean meal. In phase 2, specialty protein sources and the lactose level were reduced, and diets contained 22.4% soybean meal. Phase 3 was a typical corn-soybean meal-based diet with no specialty protein sources. Through the course of this trial, pigs were of good health with few mortalities. No interactions were observed (P > 0.10) between phase feeding budget and BW category for any response criteria. There was no significant effect (P > 0.10) of the nursery phase feeding budget on overall performance; however, pigs fed the low feeding budget program had greater (P = 0.018) fecal dry matter on d 10 than those fed the medium phase feeding budget. Feed cost and feed cost/lb of gain decreased as phases 1 and 2 feed budgets decreased (P < 0.001). No differences (P = 0.822) were observed for revenue between phase feeding programs. For income over feed cost (IOFC) no differences (P = 0.301) were observed between any phase feeding budget program. The overall d 41 BW, ADG, ADFI, feed cost, revenue, and IOFC increased (P < 0.001) as weaning BW category increased. However, no differences (P > 0.10) were observed between any BW category for F/G and feed cost/lb of gain. In conclusion, for a high-health group of pigs, the phase feeding budget program did not significantly impact nursery performance, but economics and d 10 fecal dry matter improved for pigs fed the low phase feeding program. Pigs that were heavier at weaning had better overall nursery performance and economical return than lighter pigs.
Keywords: Fecal dry matter; feed budget; growth performance; nursery pig; phase feeding